Advantages and Challenges of Queer Scholars Doing Qualitative Queer Criminology and Criminal Justice Research. (February 2023) - Rogers, Sarah A.; Rogers, Baker A.
Qualitative researchers encounter obstacles related to publishing, acceptability, research self-disclosure, rapport development, feelings of guilt or vulnerability, and opportunity that quantitative scholars often do not. Here we discuss our experiences with these obstacles related to one queer qualitative study in hopes that it will provide knowledge to the next generation of queer qualitative scholars. We begin by discussing the state of the field in terms of qualitative scholarship and queer criminology, then we discuss our own experiences doing qualitative queer criminology. Our goal is to show why qualitative queer criminology matters, that it can be done despite its challenges, and to encourage the field of criminology and criminal justice to become more inclusive of qualitative methodologies.